Ответы и объяснения

  • Участник Знаний
2013-04-15T11:13:33+04:00

1)

(√a)^2 : (a^7)^1/6  = a^2/3 : a^7/6 = a^ (2/3-7/6) =a^(-1/2)= 1/√a  или =√a/а

2)

a^8/3 * (a^1/3)^4 =a^8/3 * a^4/3 = a^(8/3+4/3) =a^12/3 =a^4

3)

128^1/3 / 2^1/3 = (128/2)^1/3 =64^1/3 = (4^3)^1/3 = 4

4)

81^-0.5 * 27^-7/12 * 9^7/8 = (3^4)^-0.5 * (3^3)^-7/12 * (3^2)^7/8 =

= 3^-2 * 3^-7/4 * 3^7/4 = 3^(-2-7/4+7/4) =3^-2 =1/9

5)

(  a^-3/4 * a^1/2  / a^5/12  *  a^5/6 /a^-1/6 )^3 =

=(  a^(-3/4+1/2-5/12)  *  a^(5/6+1/6) )^3 =

=(  a^-2/3 *  a )^3 =

=(  a^(1-2/3) )^3 =

= (  a^1/3 )^3 = a^(1/3 * 3)=

= a

6)

|a| = √ ( 3^2 +3^2 + (-3)^2 ) =√ (3*9) = √ (3*3^2) = 3√3

ответ |a| = 3√3